2003
DOI: 10.1124/mol.64.6.1410
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of μ Opioid Receptor Gene by cAMP Pathway

Abstract: The utility of morphine for the treatment of chronic pain is hindered by the development of tolerance. Fentanyl has been shown to be a potent analgesic with a lower propensity to produce tolerance and physical dependence in the clinical setting. Previous finding has shown that fentanyl induces opioid receptor gene expression in PC-12 cells (Brain Res 859:217-223, 2000). In this report, we aim to identify the molecular mechanism of -opioid receptor (MOR) gene regulation by fentanyl. We demonstrated that the 4.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 39 publications
2
32
0
Order By: Relevance
“…Activation of the Jak-Stat pathway (Friedman and Halaas 1998) as well as the cAMP pathway (Zhao et al 2002) are associated with leptin signaling in the hypothalamus. The promotor region of the MOR gene contains potential cytokine response elements (Roy et al 1992) as well as cAMP response elements (Lee and Lee 2003), suggesting that these pathways could regulate MOR expression following leptin receptor activation. Downregulation of leptin receptor mRNA in the VTA following a high fat diet may result in reductions of cytokine and or cAMP-mediated mu-opiate receptor gene expression, although further studies are necessary to elucidate this mechanism of regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the Jak-Stat pathway (Friedman and Halaas 1998) as well as the cAMP pathway (Zhao et al 2002) are associated with leptin signaling in the hypothalamus. The promotor region of the MOR gene contains potential cytokine response elements (Roy et al 1992) as well as cAMP response elements (Lee and Lee 2003), suggesting that these pathways could regulate MOR expression following leptin receptor activation. Downregulation of leptin receptor mRNA in the VTA following a high fat diet may result in reductions of cytokine and or cAMP-mediated mu-opiate receptor gene expression, although further studies are necessary to elucidate this mechanism of regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, several papers indicated that the region of Ϫ250 to ϩ1 bp in the mouse MOR proximal promoter is important for regulation of mouse MOR (Ikeda et al, 2001;Lee and Lee, 2003). The molecular mechanisms responsible for MOR reg-ulation in this region are not well known, and therefore this study focuses on this regulatory region.…”
Section: Identification Of a Regulatory Element (؊250 To ؉1)mentioning
confidence: 99%
“…For example, our lab has identified multiple regulatory elements in the MOR promoter region, such as Sp1 (Ko et al, 1998), single-stranded DNA-binding site (Ko and Loh, 2001), Sox (Hwang et al, 2003), PU.1 , neuronrestrictive silencer factor , and Sp3 isoforms (Choi et al, 2005). Regulatory sequences in the 5Ј-UTR have also been defined by other labs, including STAT6 (Kraus et al, 2001), cAMP response element-binding protein (Lee and Lee, 2003), and neurorestrictive suppressor element (Andria and Simon, 2001). However, studies of its 3Ј-UTR have been very limited.…”
mentioning
confidence: 99%